Streptococcus bovis complex isolated from pleural fluid in a case of liver cirrhosis: An interesting case report - -, Sunayana (Indian Journal of Case Reports, 2024)
Organisms belonging to Streptococcus bovis complex have been under-rated as pathogens. This report focuses on an organism belonging to this complex isolated from the pleural fluid of an adult patient with liver cirrhosis. Various organisms from this group have been associated with bacteremia, infective endocarditis, peritonitis, and meningitis. These are well-known to be associated with hepatobiliary disease and grown from various body samples but their growth from the pleural fluid is thought-provoking and confirms their pathogenic potential in such patients. Furthermore, reporting it from the pleural fluid is unique in literature.